Associated factors and effectiveness of intervention program for job dissatisfaction among teachers of the disabled at community-based rehabilitation centers in Kelantan - Bakri, Noraziah (2011)
Introduction: Job satisfaction is associated with much important conducts that have implications for individual and organizational. Many researches believed that psychological characteristics are of the most pervasive and influential health hazard and among all, job stress and dissatisfaction are the two factors most frequently found to be associated with various adverse health outcomes. Occupations related to human services tend to be affected in the same way as other occupations. The aims of this study were to determine the prevalence of job dissatisfaction and associated factors of teachers at community-based rehabilitation centers (CBRs) and to evaluate the effectiveness of intervention program on job dissatisfaction. Methods: This study was involving cross-sectional and pre and post-intervention study designs of 32 teachers of 28 CBRs in Kelantan. Pre-intervention stage requiring participants to complete Job Content Questionnaires (JCQ) for preliminary assessment. Subsequent intervention consisted of aerobic exercise, talks on stress and its management and stress management in religion and spiritual perspectives, video show session, group discussion and question and answer sessions and pamphlets distribution was carried-out. Job dissatisfaction level was reassessed at immediate-post and 6-weeks-post intervention using the same instrument. Multiple linear regression (MLR) analysis was done to determine associated factors related to job dissatisfaction while repeated measure ANOVA analysis-- time effect was done to determine the effectiveness of intervention. Results: The mean (SD) age of respondents was 34.87(8.18) years and the median (IQR) working duration of current job position was 24 (12) months. The prevalence of job dissatisfaction was 31.3% (95% CI 0.17, 0.47) with mean (SD) score of job dissatisfaction 0.263 (0.13). Age and skill discretion were found to have linear relationship with job dissatisfaction. In assessment of effectiveness of intervention program, it was found that the job dissatisfaction score was significantly reduced at the immediate post-intervention (p < 0.016) but not at 6 weeks post-intervention although it was lower than pre-intervention. Conclusion: Age and skill discretion are associated with job dissatisfaction. A shortcourse intervention program had been found to be able to reduce job dissatisfaction among these teachers of which the change was significantly seen at the immediate postintervention.